2015
DOI: 10.1007/s00253-015-6503-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and regulation of the catalytic promiscuity of (−)-γ-lactamase from Microbacterium hydrocarbonoxydans

Abstract: Mhg, a previously reported (-)-γ-lactamase from Microbacterium hydrocarbonoxydans, was identified to have perhydrolase activity by combining structure similarity search with activity assays. Kinetic studies illustrated that perhydrolysis was the native activity owing to lower K m and higher k cat/K m values. Experimental evidence showed that both hydrolysis and perhydrolysis reactions took place at the same active center. Engineering of the putative substrate-binding pocket revealed that Leu233 site played a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Plasmid pBAD/M with a C-terminal 6×His tag was used to overexpress Cbp1 in E. coli Top10 (Sun et al, 2015). A DNA fragment encoding Cbp1 was amplified from A. caulinodans ORS571 genomic DNA with the primer pair Cbp1- Nde I-F/ Hin dIII-R and cloned into the Nde I/ Hin dIII site of pBAD/M to create the recombinant expression plasmid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid pBAD/M with a C-terminal 6×His tag was used to overexpress Cbp1 in E. coli Top10 (Sun et al, 2015). A DNA fragment encoding Cbp1 was amplified from A. caulinodans ORS571 genomic DNA with the primer pair Cbp1- Nde I-F/ Hin dIII-R and cloned into the Nde I/ Hin dIII site of pBAD/M to create the recombinant expression plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…The Cbp1R320A mutant was generated using the QuikChange ® Site-Directed Mutagenesis Kit (Stratagene) with the primer pair Cbp1R320A-F/R. Protein expression was induced with 0.1% L-arabinose and incubation at 16°C for 24 h. Protein purification was performed as described previously (Sun et al, 2015). Proteins were analyzed by SDS-PAGE and their concentration was measured using the standard BCA protein assay.…”
Section: Methodsmentioning
confidence: 99%
“…1) and that its catalytic efficiency as a perhydrolase was 10-fold higher than as a ␥-lactamase. Active site mutagenesis confirmed that the two reactions occur in the same active center (15). Structure analysis revealed that Mhg shares high structural similarity with an aryl esterase from Pseudomonas fluorescens and that both have the same Ser-His-Asp catalytic triad.…”
mentioning
confidence: 72%
“…Over the past 30 years, numerous lactamases have been isolated and applied in the ring-opening of Vince-lactam. [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] Resolution could, alternatively, be achieved using a variety of other enzymes including CAL-B and a non-haem chloroperoxidase from Streptomyces viridochromogenes. [119][120][121][122] CAL-B resolution efficiency could be increased by making use of the activated N-hydroxymethyl Vince-lactam.…”
Section: Scheme 10mentioning
confidence: 99%